Cognitive ability and learning to play equilibrium: a level-k analysis - Gill, D; Prowse, V (University of Oxford, 2013)
In this paper we investigate how cognitive ability influences behavior, success and theevolution of play towards Nash equilibrium in repeated strategic interactions. We study behaviorin a p-beauty contest experiment and find striking differences according to cognitiveability: more cognitively able subjects choose numbers closer to equilibrium, converge morefrequently to equilibrium play and earn more even as behavior approaches the equilibriumprediction. To understand better how subjects with different cognitive abilities learn differently,we estimate a structural model of learning based on level-k reasoning. We find asystematic positive relationship between cognitive ability and levels; furthermore, the averagelevel of more cognitively able subjects responds positively to the cognitive ability of theiropponents, while the average level of less cognitively able subjects does not respond at all.Our results suggest that, in strategic environments, higher cognitive ability translates intobetter analytic reasoning and a better 'theory of mind